The Performance of the Clinical Disease Activity Index in Patients with Rheumatoid Arthritis - Rezzan Günaydın,; Altınay Göksel Karatepe,; Taciser Kaya, (Archives of Rheumatology, 2006)
Objective: This study was performed in order to investigate the agreement between the Clinical Disease Activity Index (CDAI) which has been developed recently to observe the disease activity in patients with rheumatoid arthritis (RA) and the other indices which are the Simplified Disease Activity Index (SDAI) and DAS28, and to study the relation among the CDAI, acute phase reactants and functional status. Patients and Methods: 73 cases followed with the diagnosis of RA were enrolled in the study. The scores of the CDAI, the SDAI and DAS28 were calculated. The functional status was assessed with the Health Assessment Questionnaire (HAQ). The cases were assigned to the 20% of segments based on their scores of all three indices. The cases were also classified according to their levels of disease activity (remission, low, moderate, or high disease activity). The agreement among the CDAI, DAS28 and the SDAI were assessed with weighted kappa statistics, and the relation among the CDAI, ESR, CRP and functional status were examined using the Spearman's correlation analysis. Results: In the groups which were composed according to both the 20% of segments and the levels of disease activity, the agreement between the CDAI and DAS28 was assessed as “good” (κ = 0.765 and 0.705, respectively). The agreement between the CDAI and the SDAI were obtained as “excellent” in both groups (κ = 0.876 and 0.891, respectively). It is observed that a positive correlations among the CDAI, ESR, CRP and HAQ scores (r = 0.284 p = 0.015, r = 0.275 p = 0.018, r = 0.459 p = 0.000, respectively). Conclusion: It is concluded that the CDAI could be employed for determining the disease activity in patients with RA, especially in routine practice, in terms of acceleration for therapeutic decision making or changing for any time and anywhere, without requiring any calculator or laboratory assessment. (Rheumatism 2006; 21: 45-8)